Study of Moderation Verses in the Perspective of Nusantara Tafsir - Syaifuddin, Mohammad; Taufiq, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study provides an understanding and interpretation of the verses of moderation in the opinion of the commentator or commentator in the archipelago. The Qur’an is not a final product, it is necessary to carry out the activities of intellectual diligence in the form of “interpretation” because the lip of the Qur’an cures me all my time to eat. Social interaction as the basic capital and characteristics of the social humanity of Muslims through understanding the verses contained in the Qur’an is a solution to the hope of divine pleasure and the achievement of correct understanding. The difference is the flavor of understanding, because some interpretations of the verses of the Qur’an tend not to be moderate in interpretation. As a moderate Muslim discussing verses of moderation, he will generate a moderate character in personality and personality that mediates the two tensions in the epistemology of interpretation between the text and the liberal. ntolerant beliefs and attitudes in the world and views of life began to emerge at the primary and secondary levels. The emergence of intolerance in religion as one of the factors is the lack of understanding and practice on the largest possible scale in the content, meaning, and context of the Qur’an itself and in matters related to the interpretation of the verses of moderation and moderation.